2022
DOI: 10.3390/horticulturae8080746
|View full text |Cite
|
Sign up to set email alerts
|

Jania adhaerens Primes Tomato Seed against Soil-Borne Pathogens

Abstract: Managing soil-borne pathogens is complex due to the restriction of the most effective synthetic fungicides for soil treatment. In this study, we showed that seed priming with Jania adhaerens water-soluble polysaccharides (JA WSPs) was successful in protecting tomato plants from the soil-borne pathogens Rhizoctonia solani, Pythium ultimum, and Fusarium oxysporum under greenhouse conditions. WSPs were extracted from dry thallus by autoclave-assisted method, and the main functional groups were characterized by us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 70 publications
0
1
0
Order By: Relevance
“…Some authors showed that alga extracts can enhance the growth, yield, and nutritional quality of radish plants and improve the yield, leaf photosynthesis, and ripening time of tomato. , Seaweed extracts are a mixture of biologically active substances, such as alginates, vitamins, proteins, free amino acids, polyphenols, and micro- and macro-elements that may be involved in plant growth stimulation. Several studies have described the use of brown alga extracts to enhance the growth, yield, and nutritional quality of horticultural plants. Some of them regard extracts from algae belonging to the Sargassum genus. , Mahmoud et al reported that radish seed and leaf treatment with Sargassum vulgare extract increased vegetative growth as well as chlorophyll and carotenoid content. On tomato, soil treatment with an extract from Sargassum horneri improved yield, leaf photosynthesis, and ripening time of tomato .…”
Section: Introductionmentioning
confidence: 99%
“…Some authors showed that alga extracts can enhance the growth, yield, and nutritional quality of radish plants and improve the yield, leaf photosynthesis, and ripening time of tomato. , Seaweed extracts are a mixture of biologically active substances, such as alginates, vitamins, proteins, free amino acids, polyphenols, and micro- and macro-elements that may be involved in plant growth stimulation. Several studies have described the use of brown alga extracts to enhance the growth, yield, and nutritional quality of horticultural plants. Some of them regard extracts from algae belonging to the Sargassum genus. , Mahmoud et al reported that radish seed and leaf treatment with Sargassum vulgare extract increased vegetative growth as well as chlorophyll and carotenoid content. On tomato, soil treatment with an extract from Sargassum horneri improved yield, leaf photosynthesis, and ripening time of tomato .…”
Section: Introductionmentioning
confidence: 99%
“…The disease severity caused by RS was evaluated by scoring the root apparatus based on a 0-5 scale(Righini et al 2022b), where: 0 = absence of necrosis (0% of symptoms); 1 = very slight necrosis (up to 5% of root with symptoms); 2 = slight necrosis (6-20% of root with symptoms); 3 = moderate necrosis (20-50% of root with symptoms); 4 = severe necrosis (51-70% of root with symptoms); 5 = severe crown and root necrosis (> 70% of root with symptoms The experiment was repeated three times (n = 3).…”
mentioning
confidence: 99%